PERFORMATIVE ANALYSIS OF RAJAH SYEKH SUBAKIR IN TAWING VILLAGE, TRENGGALEK PERSPECTIVE OF LIVING QUR'AN - Nurul Himatil ‘Ula; Senata Adi Prasetia (Jurnal Studi Ilmu-ilmu Al-Qur'an dan Hadis, 2020)
Al-Qur'an is accepted by the public in various forms. One of them by using a few pieces of verse as part of the protection spell. The use of al-Qur'an in this function is manifested in the face of Sheikh Subakir in Tawing Village, Trenggalek. This study aims to find the process of changing the rajah tradition which is the result of acculturation of Javanese culture and Islamic values as well as the meaning of society towards rajah, and receptions of the verses of the Koran as pager omah (house protection). This research is a field research with descriptive-analysis method, analyzed using social construction theory of reality by Peter L. Berger and Thomas Luckmann. The results showed that the people of Tawing Village used the rajah of Sheikh Subakir as a pager omah. The phenomenon of the rajah of Sheikh Subakir is not only meant as a house protection or cultural acculturation, but also acts as a social cohesion that unites the local community. In fact, this tradition influences a set of people’s beliefs about feeling safe, belief in protection, and reinforcement in their social structure.